Kerja Sama Internasional dalam Penanggulangan Kejahatan Siber: Urgensi Ratifikasi Konvensi Budapest dan Pembentukan Rezim Kolaboratif bagi Indonesia - Gilang Rizki Aji Putra (UIN Jakarta, 2024)
Cybercrime transcends territorial boundaries, constituting a transnational threat that demands coordinated international responses. This article analyzes the framework of international cooperation in combating cybercrime, evaluates Indonesia’s position within the global architecture, and formulates strategic measures to strengthen its engagement. Using normative legal research with statutory, conceptual, and comparative approaches, the study finds that the Budapest Convention on Cybercrime (2001) remains the most comprehensive multilateral instrument, providing a foundation for harmonizing substantive and procedural law as well as enabling rapid cooperation mechanisms. As Indonesia currently holds observer status, structural limitations persist, including delays in Mutual Legal Assistance (MLA) processes and lack of direct access to the 24/7 point-of-contact network. Analysis of cross-border cyber incidents affecting Indonesia demonstrates that without seamless cooperation, enforcement efforts frequently stall at issues of attribution and jurisdiction. The article concludes that accession to the Budapest Convention, coupled with domestic legal harmonization and proactive cyber diplomacy, is essential. Keywords: Transnational Cybercrime, Budapest Convention, Mutual Legal Assistance, International Cooperation, Jurisdiction.